(3GdZQjH GdeUfas - (3GdbGSe Hf SdGe GdgQhj GdCROj GdNRGYj, CHh YHjO, J (B224 (3g` s
(3ChdgG (B:s
(3MOKfG CMeO Hf MeGO bGd bGd dfG Ydi Hf YHO GdYRjR bGd SeYJ gPG GdcJGH bQCI Ydnj CHj YHjO GdbGSe Hf SdGe ZjQ eQI hSCdJg jQhi Yfg eG bQF Ydjc abGd s
(3BNQgG (B:s
(3jfJgi Hbhdg (B: ( (3hbGd (B: (3CHh YHjO ai MOjK GHQGgje djS ai GdQHGFH UObI (B) s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B101s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1209s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs